Possibilities of Pulse Wave Contour Analysis in Diagnostics of Early Vascular Aging - A. M. Tuktarov; A. E. Filippov; A. A. Obrezan; L. V. Kukol' (Рациональная фармакотерапия в кардиологии, 2020)
Aim. To study the possibilities of photoplethysmography (PPG) in evaluation of arterial stiffness, arterial age and early vascular aging (EVA) in healthy individuals and patients with cardiovascular risk factors.Material and methods. The material of the study was the data from a survey of large teams undergoing medical examination in a group of clinics of Medical Center “SOGAZ”. A total of 783 men aged from 20 to 92 years were examined. The mean age was 48.2±10.32 years. PPG was used as a special research method, performed using the AngioScan-01 diagnostic complex. The following indicators were evaluated: stiffness index (SI), reflection index (RI), augmentation index (Alp75), age index (AGI) and pulse wave types (PV-type). For determining the vascular age (VA), correlation field of the dependence of AGI on the age of the subject was built, and then the VA was calculated by the value of the AGI.Results. The greatest correlation with passport age was revealed for the AGI indicator (r=0.54) at the first stage of the study. EVA-syndrome criteria were considered as values of the AGI, beyond the 90th percentile (n=65), and the criteria for “young vascular age” (n=87) were AGI values below 10 percentile with age correction. Comparison of these two alternative subgroups (in men aged from 40 to 59) in terms of arterial stiffness showed significant differences in SI (8.2±0.99 vs 7.6±0.89, respectively, p=0.001), Alp75 (-0.2±14.54 vs 20.5±10.31, respectively, p=0.0001), PV-type. The frequency of detection of multiple risk factors according to the results of questionnaires and laboratory diagnostics in patients with EVA-syndrome was also significantly higher. Assessment of the contribution of vascular risk factors to vascular aging showed that the leading positions are occupied by hypertension, hypertriglyceridemia, abdominal obesity, hyperglycemia, and smoking.Conclusion. PPG is a simple, fast, and informative method that allows to evaluate the parameters of the vascular wall stiffness. It can be assumed that its use in screening examinations of middle-aged men can help in identifying patients requiring observation and intensive prevention.